Lovastatin Alleviates α-Synuclein Aggregation and Phosphorylation in Cellular Models of Synucleinopathy - Dai, Lijun; Wang, Jiannan; He, Mingyang; Xiong, Min; Tian, Ye; Liu, Chaoyang; Zhang, Zhentao (Frontiers in Molecular Neuroscience, 2021)
Parkinson’s disease (PD) is one of the most common neurodegenerative diseases. Pathologically, it is characterized by the aberrant aggregation of α-synuclein (α-syn) in neurons. Clinical evidence shows that patients with hypercholesterolemia are more likely to get PD, while lovastatin users have a lower risk of suffering from it. In this study, we investigated the effects of lovastatin on the aggregation and phosphorylation of α-syn in vitro. Our results demonstrate that α-syn preformed fibrils induce the phosphorylation and aggregation of α-syn in HEK293 cells stably transfected with α-syn-GFP and SH-SY5Y cells as well, which could be attenuated by in a concentration-dependent manner. Besides, lovastatin inhibited oxidative stress, histone acetylation, and the activation of casein kinase 2 (CK2). Collectively, lovastatin alleviates α-syn aggregation and phosphorylation in cellular models of synucleinopathy, indicating its potential value of being adopted in the management of PD.